PERANAN MINAT BELI DALAM MEMEDIASI KESADARAN MEREK LAYANAN CASH ON DELIVERY DAN EXPERIENTIAL MARKETING TERHADAP KEPUTUSA PEMBELIAN PADA LIVE TIKTOK HIKMAH_STORE - Hotijah Husnul Hikmah; Yudha Praja; Siti Soeliha (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Hotijah Husnul Hikmah. Student ID 202113272. "The Role of Purchase Intention in Mediating Brand Awareness, Cash on Delivery Service, and Experiential Marketing toward Purchase Decision of Handmade Products on TikTok Live Hikmah_Store" This study aims to examine the role of purchase intention in mediating the influence of brand awareness, Cash on Delivery (COD) service, and experiential marketing on purchase decisions of handmade products during TikTok Live sessions at Hikmah_Store. The sampling technique used in this study is simple random sampling (SRS) with a total of 200 respondents. Data analysis and hypothesis testing were conducted using the Structural Equation Modeling - Partial Least Squares (PLS-SEM) approach. The results show that brand awareness has a negative and insignificant effect on purchase intention. Cash on Delivery service has a positive but insignificant effect on purchase intention. Experiential marketing also has a positive but insignificant effect on purchase intention. However, brand awareness, Cash on Delivery service, and experiential marketing have positive and significant effects on purchase decisions. Meanwhile, purchase intention has a positive but insignificant effect on purchase decisions. Additionally, the indirect effect of brand awareness, Cash on Delivery service, and experiential marketing on purchase decisions through purchase intention is not significant.